2016
DOI: 10.4269/ajtmh.16-0174
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion to Causes of Febrile Illness in Mongolian Peacekeepers Deployed to South Sudan

Abstract: Abstract. Immediately before deployment (Fall 2012) and after deployment (Spring 2013) in support of United Nations peacekeeping operations, Mongolian Armed Forces medical personnel obtained serum samples from the first contingent of Mongolian peacekeepers deploying to South Sudan to monitor serologic evidence of exposure to diseases that cause acute febrile illness. A total of 632 paired samples were tested for IgG antibody for the following (number of seroconversions in parentheses): Rickettsia (spotted fev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…In summary, chikungunya virus infections are realistic threats to deployed soldiers in endemic areas due to the vector-borne mode of transmission. Apart from outbreak settings, however, the frequency of transmission in deployed soldiers in the tropics seems to be low [23,24]. Comparisons with other arbovirus infections are problematic.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, chikungunya virus infections are realistic threats to deployed soldiers in endemic areas due to the vector-borne mode of transmission. Apart from outbreak settings, however, the frequency of transmission in deployed soldiers in the tropics seems to be low [23,24]. Comparisons with other arbovirus infections are problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations on Op HERRICK (Helmand, Afghanistan) were able to find causative pathogens in febrile patients12 and identify seroconversion in well volunteers 13. Research in Mongolian troops serving in South Sudan showed seroconversion to Rickettsia , West Nile Fever, Q Fever and Leptospira , although it is unknown how many of these volunteers had symptoms 14. However, the Op HERRICK studies relied either on a frequent and reliable airbridge to return samples to the UK, or on sampling in the UK pre-deployment and post-deployment.…”
Section: Discussionmentioning
confidence: 99%
“…The legend shows the country names and their year of accession into the EAC in bracket. Non-human primates, humans [115,149,192,[195][196][197][200][201][202] Ndumu During this time there were more than 20 known arboviruses including the Yellow fever virus which were unrelated to the virus, hence it was named Bunyamwera [30,31]. The virus has spread across many regions over the past decades and remains an important virus due to its ability to cause human diseases.…”
Section: Bunyaviridaementioning
confidence: 99%
“…The virus has also been serologically detected in human sera in Tanzania [147]. Serological detection has been reported in South Sudan [148][149][150], with also no available data of the virus in Burundi [137].…”
Section: West Nile Virus (Wnv)mentioning
confidence: 99%
See 1 more Smart Citation